Efforts to Increase User Satisfaction Based on System Quality and Information Quality - Fatimah, Siti; Sariyono, Nurul; Junaedi, Arif; Ayu, Ira Porbonovitaning; Qomariah, Nurul (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
This research aims to determine and analyze the influence of system quality and data quality on data user satisfaction on the Jember Regency One Data Portal Application. The population in this study was all State Civil Apparatus in the Jember Regency Government, totaling 11,667 employees. Samples are determined using the Slovin formula. Data analysis uses descriptive analysis for respondents and research variables. The reliability test and data validity test aim to measure the research questionnaire. Research hypothesis testing was carried out to determine the effect of the independent variable on the dependent variable. The data analysis method uses descriptive analysis, validity and reliability tests, hypothesis testing. The results of this research are expected to show that system quality and information quality can increase user satisfaction.